Penerapan SAK-EP dan Kualitas Laporan Keuangan Entitas Privat di Indonesia - Ahmad Anggi Hamidi; Sri Lismawati; Zelly Denofriza; Dodi Yuli Satria; Widi Nugraha (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The transition from SAK ETAP to SAK-EP (Financial Accounting Standards for Private Entities) in Indonesia, effective January 1, 2025, represents a fundamental shift toward convergence with IFRS for SMEs. This study aims to systematically examine the impact of SAK-EP adoption on the quality of financial statements of non-public entities in Indonesia during the transition period (2021-2026), and to map the progress, obstacles, and future directions of private financial governance. A Systematic Literature Review (SLR) guided by the PRISMA 2020 protocol was conducted. A comprehensive evaluation was performed on 28 peer-reviewed articles systematically collected from Google Scholar, Portal Garuda, and DOAJ, published between 2021 and 2026. The analysis identifies dynamic research trends shifting from conceptual-normative studies (2021-2022) to readiness studies (2023-2024), and early empirical evidence post-effective implementation (2025-2026). Regarding quality dimensions, 71.4% of studies confirm increased value relevance, and 90.5% note improved comparability due to convergence with IFRS for SMEs. However, reliability and timeliness show ambiguous results with temporary declines in low-capacity entities. The study concludes that five key contextual factors HR competence, business scale, external support, sector type, and geographic location significantly moderate adoption success. This study provides a roadmap for IAI, regulators, and professional associations to design asymmetric mentoring programs focusing on regions outside Java.